Teak Trees as Source of Inspiration for Developing Batik Motifs - Mulyanto, Mulyanto; Hartono, Lili; Murni, Endri Sintiana; Handayani, Endang Sri; Nurcahyanti, Desy (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
Many batik motifs have been developed in various regions, inspired by various local resources such as plants, animals, regional icons, cultural arts, etc. The objective of this study is to look for ideas in the form of teak leaves and flowers that can be developed into batik and textile motif designs. The descriptive qualitative, literature review, participatory follow-up study, focus group discussion method, and the development of craftsman creativity were all used to achieve these goals. The study took place at the Jalidin batik craft shop in Sragen. Teak plant objects, motif designers, batik craftsmen, and libraries were among the data sources. The findings of the study were the motifs in the form of teak leaves and flowers, which could be used as master designs for both batik and textiles. Then the shape of the teak leaves and flowers are arranged in various compositions to produce several designs, and the batik motif designs are applied to jarit-patterned batik, long-sleeved shirt-patterned batik, and textile/printed batik. The resulting motifs were then produced into batik according to the economic class projections of the consumers, namely the consumer’s economic class projections, using prima and primissima cloths, combination and writing techniques, synthetic and natural dyes, and synthetic and natural dyes. In addition, the motifs were produced into printed textiles/batik. Batik cloths and textiles that have been produced are then made into shirts.